SCALING UP A MOBILE TELEMEDICINE SOLUTION IN BOTSWANA: KEYS TO SUSTAINABILITY - Kagiso eNdlovu; Kagiso eNdlovu (Frontiers Media S.A., 2014)
Effective health care delivery is significantly compromised in an environment where resources, both human and technical, are limited. Botswana's health care system is one of the many in the African continent with few specialised medical doctors, thereby posing a barrier to patients' access to health care services. In addition, the traditional landline and non-robust Information Technology (IT) network infrastructure characterised by slow bandwidth still dominates the health care system in Botswana. Upgrading of the landline IT infrastructure to meet today's health care demands is a tedious, long and expensive process. Despite these challenges, there still lies hope in health care delivery utilising wireless telecommunication services. Botswana has recently experienced a tremendous growth in the mobile telecommunication industry coupled with an increase in the number of individually owned mobile devices. This growth inspired the Botswana-UPenn Partnership (BUP) to collaborate with local partners to explore using mobile devices as tools to improve access to specialised health care delivery. Pilot studies were conducted across four medical specialties, including radiology, oral medicine, dermatology and cervical cancer screening. Findings from the studies became vital evidence in support of the first scale-up project of a mobile telemedicine solution in Botswana, also known as Kgonafalo. Some technical and social challenges were encountered during the initial studies, such as malfunctioning of mobile devices, accidental damage of devices and cultural misalignment between IT and healthcare providers. These challenges brought about lessons learnt, including a strong need for unwavering senior management support, establishment of solid local public-private partnerships, and efficient project sustainability plans. Sustainability milestones included the development and signing of a Memorandum of Understanding (MOU) between the Botswana government and private telecommuni